(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
The testis, a vital reproductive organ in males, is highly susceptible to damage from chemotherapy. The root of Curculigo latifolia contains secondary metabolites that have potential as anticancer agents and protective agents for reproductive health. This study aims to evaluate the protective potential of crude extract from C. latifolia in suppressing testicular carcinogenesis induced by DMBA in vivo. This study employed a completely randomized design with five treatment groups, including negative and positive controls, as well as three treatment groups receiving doses of C. latifolia root extract at 300, 600, and 900 mg/Kg body weight. Testicular carcinogenesis was induced by oral administration of DMBA at a dose of 20 mg/Kg body weight twice a week for six weeks. The data of sperm quality, including motility, viability, sperm concentration, and testicular microanatomical structures, analysed by ANOVA one-way test, revealed significant effects from oral administration of C. latifolia root extract (p < 0.05). Overall, C. latifolia root extract improves sperm quality and protects the testicular microanatomical structure against DMBA exposure. Novelty in this study explores the local herbal agent potential (C. latifolia root extract), decreasing reproductive damage and alopecia from DMBA carcinogenic effects. Thus, these findings directly contribute to reaching Sustainable Development Goal 3 (SDG3) by ensuring healthy lives and promoting well-being in all aspects for all ages.